Edukasi Adaptasi Kebiasaan Baru Pada Masa Pandemi Covid-19 - Sri Mulyaningsih; Lida Amalia; Hudiana Hernawan; De Budi Irwan Taofik; Dewi Hernawati (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
Indonesia and other countries in the world are currently facing a deadly disease outbreak, namely Covid-19. This outbreak is known as the Covid-19 pandemic. The number of victims who died in Indonesia has more than 250 thousand people. Until now, there is still no medicine or vaccine that can cure this disease. Therefore, the number of victims who die every day is still happening. This causes the corona virus that causes Covid-19 to still not disappear from people's lives. The way out to break the chain of transmission of corona virus infection is the 'new normal' adaptation. New Normal